RESTORATION OF MEMORY AND ACETYLCHOLINESTERASE ACTIVITY BY MICHELIA CHAMPACA IN CHRONICALLY NOISE STRESSED WISTAR ALBINO RATS - S, Malathi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective:The ability of an organism to adapt to aversive stressful situations or life challenging circumstances is very crucial to its state of health and survival. However, breakdown in adaptation due to persistent uncontrollable stress, leads to impairment of bodily functions and onset of a variety of pathological disorders especially memory decline. This study was designed to evaluate the effect of Michelia champaca(M.champaca) a potent antioxidant on chronic noise stress induced memory impairment in rats. Methods: Male wistar albino rats were used in this study. Animals were exposed to noise for 30 consecutive days (4hrs/day) before testing for memory. Thereafter, the plasma corticosterone level and acetylcholinesterase activity were estimated in the three discrete regions of the brain homogenate using spectrophotometer. Result:Our results showed that M.champaca prevented memory impairment and suppressed corticosterone concentrations induced by chronic noise stress. Moreover it also decreased brain acetylcholinesterase activity when compared with chronic stress group (p < 0.05). Conclusions:These findings suggest that M.champaca attenuates memory deficits induced by chronic noise stress in albino rats and may be useful therapeutically for stress-related cognitive dysfunctions. The reduction in the levels of serum corticosterone and inhibition of cholinesterase enzyme might be contributing significantly to the positive effect of M.champaca on memory in rats exposed to chronic noise stress. Keywords: M.champaca, memory, corticosterone, chronic noise stress, acetylcholinesterase activity, Eight-arm radial maze.